DNA barcodes foster collaborative networking in Argentina: from evolutionary biology to invasive species and pathogen identification in food production - Lavinia, Pablo D. (2024)
Fil: Lavinia, Pablo D. Universidad Nacional de Río Negro, Laboratorio de Investigación y Conservación de la Biodiversidad (UNRN–InCoBIO), Sede Atlántica, Viedma, Río Negro, Argentina